(untitled) (Lund, Sweden, 1981)
This is the first volume from a series of three conferences which will focus on technology and industrial policy in China an Europe.
Keywords: Industrial policy,Industrial policy,Chính sách công nghiệp,Chính sách công nghiệp; Congresses,Congresses,Hội nghị,Hội nghị; China,Europe,Trung Quốc,Châu Âu